Formation of Cu-Al layered materials by detonation spraying and modification of the interface by annealing/spark plasma sintering - Dudina Dina V.; Ulianitsky Vladimir Yu.; Tokarev Vadim G. (Science of Sintering)
Cu-Al layered structures are frequently encountered in electrical and electronic devices and facilities as both metals possess a high electrical conductivity. In the present work, a new approach was used to fabricate Cu-Al bi-layers. The layers were formed by successively depositing copper and aluminum on a steel substrate by detonation spraying. The layered structures were annealed in a vacuum furnace or treated by electric current in a spark plasma sintering (SPS) facility. Both furnace annealing and SPS induced the formation of Cu-Al intermetallics, the thickness of the product layers being greater after the SPS treatment. The effect of applied pressure alone could not fully account for the difference between the outcomes of furnace annealing and SPS. The main products formed during both annealing and SPS were CuAl2 and Cu9Al4. The application of pressure during SPS allowed eliminating the interfacial porosity. Conventional annealing was not instrumental for this purpose.